Photoelectric and Electrical Properties of Composite Materials Based on n-InSe and Graphite - Камінський, В.М.; Боледзюк, В.Б.; Водоп’янов, В.М.; Савицький, П.І.; Заслонкін, А.В.; Заполовський, М.В. (Сумський державний університет, 2021)
This paper presents the results of research of composite materials and structures made on the basis of layered semiconductors and graphite. These materials have a similar crystalline structure and due to their unique physical properties are promising for electronics and photoelectronics. Therefore, the idea of mak ing new composite materials and structures based on them is quite obvious. We have tried to take some steps in this direction using various technological operations. Three types of samples were prepared: pressed tablets of mixed powders of InSe and thermoexpanded graphite; graphite films from aqueous sus pension of thermoexpanded graphite, which were deposited onto fresh cleavage InSe (0001) surface, and graphite/InSe structures obtained by vacuum deposition. Their photoelectric and electrical properties have been investigated. A significant increase in the electrical conductivity of InSe-thermoexpanded graphite composite material relative to the initial InSe powder has been found. This means that in this material an electric current flows through the channels formed by graphite, and the selected pressure at which the samples were prepared provides good contact between individual crystallites. The photosensitivity of the obtained materials and structures is determined by the optical properties of InSe. The photosensitivity range of InSe-thermoexpanded graphite composite material is smaller than that of InSe or structures due to scattering at grain boundaries.
Keywords: Indium selenide, Thermoexpanded graphite, Composite material, Photosensitivity, Electrical conductivity